Public Relations Management Strategy in Improving School Quality at State Vocational School 1 Siabu - Putriana Nasution; Faisal Musa; Afridah (Social Science Academic, 2026)
This study aims to determine the public relations (PR) management strategy implemented at SMK Negeri 1 Siabu in an effort to improve school quality. The background of this study is the importance of the role of Public Relations in building communication between schools and various external parties such as parents, the industrial world, government, and the community in order to create a positive image and improve the quality of education. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that (1) the public relations (PR) management strategy implemented at SMK Negeri 1 Siabu in improving school quality, the strategy includes the formation of a Public Relations team, work program planning, selection of appropriate communication media such as committee meetings, social media, and publication of school activities. (2) efforts made by SMK Negeri 1 Siabu to optimize public relations strategies to improve school quality, namely through promoting student achievements, cooperation with the community and the industrial world, and publication of school activities, Public Relations has succeeded in increasing public trust and attracting public interest in making the school a choice for quality education. (3) supporting and inhibiting factors in the implementation of public relations at SMK Negeri 1 Siabu, supporting factors in Public Relations management include leadership commitment, cooperation with stakeholders, and flagship programs that are able to attract public attention. Meanwhile, inhibiting factors include low participation of some parents and limited resources.